Pro-Growth Equity : A Policy Framework for the Twin Goals - Lopez-Calva, Luis F.; Rodríguez-Castelán, Carlos (World Bank, Washington, DC, 2016)
Growth is an important channel for poverty reduction. Policies to make growth more "inclusive" have permeated the development debate and "pro-poor growth" has been the subject of a wide range of papers in the literature, including issues related to measurement, modeling, and policy. However, the analytical and particularly empirical literature to support the idea that equity-enhancing policies have a positive effect on growth is more scarce and limited, especially on the potential policy links. This paper proposes a simple conceptual framework to identify the main elements that contribute to the income generation of households, building on the notion that growth can be seen partly as the aggregate outcome of the income generation capacity of households. The framework relies on an asset-based approach, and offers insights on how a more equitable distribution of assets and opportunities for their productive use can feed back into higher growth in the long term. Using this framework, the paper links the World Bank's twin goals to specific policy channels that have direct impacts on the income generation capacity of households, with a particular focus on households at the bottom of the income distribution. The four key policy channels include (i) implementing equitable, efficient and sustainable fiscal policy and macroeconomic management, (ii) strengthening fair and transparent institutions capable of delivering quality basic services, (iii) enabling well-functioning markets, and (iv) establishing adequate risk management instruments at the macro and household levels.